Biotechnological Phytocomplex of Zanthoxylum piperitum (L.) DC. Enhances Collagen Biosynthesis In Vitro and Improves Skin Elasticity In Vivo - Giovanna Rigillo; Giovanna Pressi; Oriana Bertaiola; Chiara Guarnerio; Matilde Merlin; Roberto Zambonin; Stefano Pandolfo; Angela Golosio; Francesca Masin; Fabio Tascedda; Marco Biagi; Giulia Baini (Pharmaceutics)
Background: Zanthoxylum piperitum (L.) DC., commonly known as Japanese pepper, is a deciduous shrub native to East Asia. Its berries are widely used as a spice, known for imparting a distinctive, tingly numbing sensation. Biologically, Z. piperitum has antimicrobial, antioxidant, and anti-inflammatory properties, and it is studied for its potential benefits in pain relief and digestive health. This study proposed a novel biotechnological Z. piperitum phytocomplex (ZPP) obtained by plant cell culture for skin health, specifically targeting collagen synthesis, extracellular matrix stability, and resilience against cellular stress. Given the bioactivity of Z. piperitum, we aimed to analyze its efficacy as a sustainable alternative for skin-supportive applications in cosmetics and supplements. Methods: ZPP was produced through stable plant cell cultures, yielding a lignan-rich (3.02% w/w) phytocomplex. Human fibroblasts (HFFs) were treated with varying ZPP concentrations to assess cellular viability, collagen metabolism, and ECM-related enzyme activities, both under normal and cell stress conditions. The in vivo assessment was performed by measuring biophysical skin parameters such as hydration, elasticity, and roughness in female volunteers for a period of six weeks. Results: In vitro, ZPP exhibited non-cytotoxicity at all concentrations tested. Under hyperosmotic stress, ZPP reduced cellular damage, suggesting enhanced resilience. ZPP upregulated lysyl oxidase (LOX) protein levels, critical for collagen cross-linking and ECM stability, with protective effects observed under oxidative/inflammatory conditions. Additionally, ZPP selectively inhibited collagenase, attenuating collagen breakdown, though antioxidant activity was modest. In vivo evaluation highlighted improved skin hydration, elasticity, and roughness. Conclusions: ZPP shows promise as a biotechnological agent for skin health, particularly in supporting collagen integrity, ECM stabilization, and cellular resilience under stress. While further studies are needed to explore its full efficacy, especially for aging and environmentally stressed skin, these findings highlight ZPP’s potential as a new ingredient for cosmetic formulations aimed at skin care and the treatment of alterations caused by aging or environmental conditions.